Association between thyroid dysfunction and diabetic retinopathy: a two-sample bidirectional Mendelian randomization study - Jiali Chen; Jianghao Xiong; Fenfen Zhang; Wanyu Pan; Shaomin Cheng (Diabetology & Metabolic Syndrome)
Abstract Objectives To assess the association between thyroid dysfunction and diabetic retinopathy (DR), a two-sample bidirectional Mendelian randomization (MR) study utilizing the Genome-wide Association Study (GWAS) database was conducted to investigate the causal relationship between these two variables. Methods In this study, GWAS of 48,328,151 single nucleotide polymorphisms(SNP) in the European population from the IEU open GWAS database were utilized as genetic tools for investigating thyroid dysfunction. The total sample size for the study on hyperthyroidism was 460,499 (case group: 3557; control group: 456,942). The total sample size for hypothyroidism was 410,141 (case group: 30,155; control group: 37,986). In addition, the data on DR were extracted from the FinnGen Biobank, comprising a total sample size of 319,046 individuals (10,413 cases and 308,633 controls). For the forward MR analysis, hyperthyroidism and hypothyroidism were considered as exposures with DR as the outcome. Reverse MR analysis was conducted using DR as exposure and hyperthyroidism and hypothyroidism as outcomes. Methods: The main analytical approach employed inverse variance weighting(IVW), supplemented by MR-Egger, Weighted mode method, weighted median, and Simple mode. Cochran's Q test, MR-PRESSO, MR-Egger and leave-one-out analysis were used to evaluate the sensitivity and pleiotropy. Results Two-sample bidirectional MR analysis revealed a significant association between the presence of hyperthyroidism and hypothyroidism and an increased risk of DR in the forward MR analysis (IVW: OR = 1.29, 95% [CI] = 1.12–1.49, P < 0.001; OR = 1.17, 95% CI = 1.10–1.25, P < 0.001). In the reverse MR analysis, DR was found to be associated with an elevated risk of developing hyperthyroidism and hypothyroidism (IVW: OR = 1.56, 95% CI 1.38–1.76, P < 0.001; OR = 1.41, 95% CI 1.25–1.59, P < 0.001). Furthermore, most supplementary MR methods also demonstrated statistically significant differences and exhibited effect sizes consistent with those obtained from IVW. The sensitivity analysis confirmed the relative reliability of our causal findings. Conclusions Our findings provide genetic evidence supporting a bidirectional causal relationship between thyroid function and DR.